Une étude comparative de l’efficacité d’Azadirachtine (neem azal), Lambda-Cyhalothrine (Ampligo® ;; 150 ZC) ,Spinosad (TRACER 240 SC), bio-insecticides sur des populations des Aphides (Aphis gossypii). - Serisser, Hadj elghali; Khelifa, Djalel (My University, 2023)
The field of plant protection uses chemical control, which remains the most sensitive means in the fight against crop enemies, pepper plants infested by the aphid Aphis gossypii are treated with three bio-insecticide products Azadirachtin (neem azal), Spinosad (TRACER 240 SC), with an approved dose for each product. The treatments lasted 6 days, against pests (Aphids). The three bio-insecticide products (Azadirachtin, lambda-cyhalothrin, Spinosad) faced mortality of individuals from the first days. The results of our experience, the last week of treatment, the figures are (70%) under the effect of Azadirachtin, furthermore, (69%) under the effect of lambda cyhalothrin and (14%) under the effect of spinosad, all the tests applied are affected at the adult stage.
Keywords: Bio-insecticides; Aphis gossypii; Pepper; Azadirachine; Lambda